2003
DOI: 10.1002/ar.a.10126
|View full text |Cite
|
Sign up to set email alerts
|

Collagen type VI expression during cardiac development and in human fetuses with trisomy 21

Abstract: The role played by specific extracellular matrix molecules in normal endocardial cushion differentiation into valves and septa remains to be established. In this respect, type collagen VI is of particular interest because genes encoding the ␣1 and ␣2 chains are located on chromosome 21, and defects involving the atrioventricular (AV) cushions are frequent in trisomy 21. Collagen VI expression was studied in normal human embryonic and fetal hearts (5-18 weeks of development) and compared by immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 25 publications
2
55
0
Order By: Relevance
“…A detailed description of staining protocols can be found in previous publications. 11,12 All embryos, fetuses, and neonates were separated into 4 groups of successive gestational stages of development according to pregnancy duration and crown-rump-length (CRL): group 1, from 4 weeks/CRL 5 mm to 6 weeks/CRL 11 mm (nϭ2); group 2, from 6 weeks/CRL 11 mm to 10 weeks/CRL 40 mm (nϭ7); group 3, from 10 weeks/CRL 40 mm to 20 weeks/CRL 164 -170 mm (nϭ27); and group 4, from 20 weeks/CRL 164 -170 mm to birth/neonates (nϭ9).…”
Section: Methods Heartsmentioning
confidence: 99%
“…A detailed description of staining protocols can be found in previous publications. 11,12 All embryos, fetuses, and neonates were separated into 4 groups of successive gestational stages of development according to pregnancy duration and crown-rump-length (CRL): group 1, from 4 weeks/CRL 5 mm to 6 weeks/CRL 11 mm (nϭ2); group 2, from 6 weeks/CRL 11 mm to 10 weeks/CRL 40 mm (nϭ7); group 3, from 10 weeks/CRL 40 mm to 20 weeks/CRL 164 -170 mm (nϭ27); and group 4, from 20 weeks/CRL 164 -170 mm to birth/neonates (nϭ9).…”
Section: Methods Heartsmentioning
confidence: 99%
“…The cushion material will mainly condense into what is known as the membranous part of the atrioventricular septum. We have recently shown in human trisomy 21 fetal hearts, studied for their collagen VI distribution, that the membranous septum is exceptionally large in these cases (27). Ventricular outflow tract septation.…”
Section: Cardiac Septation and Chamber Formationmentioning
confidence: 98%
“…the transforming growth factor (TGF)-␤2 knockout mouse (26). In human patients, it is often found in trisomy 21 or Down syndrome patients (27,28).…”
Section: Cardiac Septation and Chamber Formationmentioning
confidence: 99%
“…These epicardium-derived cells (EPDCs) can migrate into the myocardium and differentiate into interstitial, subendocardial, and coronary adventitial fibroblasts, as well as coronary smooth muscle cells Vrancken Peeters et al, 1999). Several studies have demonstrated crucial roles of EPDCs in the formation of the compact myocardium (Kwee et al, 1995;Yang et al, 1995;Gittenberger-de Groot et al, 2000;Lie-Venema et al, 2003) and coronary development , while a morphogenic role for EPDCs in valve development has also been postulated , 2003a.…”
mentioning
confidence: 99%